TOURISM DEVELOPMENT STRATEGY IN BURU REGENCY - Istanto Setyahadi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
Buru Regency is one of the regencies in Maluku Province, and it is well-known forproducing high-quality eucalyptus oil. Buru Regency also has a number of potentialtourism objects, including natural tourism, marine tourism, agrotourism, andcultural and historical tourism, all of which can be developed as a source of revenuefor the region. The purpose of this qualitative research with a descriptive approachis to determine the influence of internal and external factors on tourism developmentand to identify the most appropriate tourism development strategy to be used in BuruRegency. The research is being conducted in tourist attractions throughout the Buru Regency, the local government and the tourism office are also the sources ofinformation. The research instrument used was observation, interviews, andquestionnaires, as well as a literature review. The data analysis technique usedSWOT, which has been based on an assessment of the factors that impact tourism inBuru Regency. The findings indicate that both internal (strength-weakness) andexternal (opportunity-threat) factors influence tourism development in BuruRegency. The mapping of internal and external factors via SWOT analysisdetermines the SO (strength-opportunity) strategy as the primary strategy choice,namely using strength (strength). Internally through the development of specialinterest tourism, network building among tourism object managers, collaborationwith local and foreign travel agents, website development, coordination betweenregional and central agencies, structuring tourism institutions, and facilitatinginvestment in the tourism sector. Other alternative strategies that the Buru Regencygovernment can use in tourism development include the WO (strategiesweaknessopportunity), ST (strength-threat), and WT (weakness-threat) that can be applied intourism development by the Buru Regency government.